2010
DOI: 10.1016/j.hcmf.2010.04.009
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Cost-Minimization Analysis of Providing Paediatric Palliative Respite Care before and after the Opening of Services at a Paediatric Hospice

Abstract: A palliative care service provider may add or decrease overall operational costs to the healthcare system. This study assessed the costs of managing respite care for children with life-limiting illness at the Children's Hospital of Eastern Ontario for the 12-month period both before and after services at Roger's House (RH, a paediatric hospice) was made available. The opening and operation of RH for providing respite care resulted in a minimization of operational costs (n = 66 patients, mean decrease of $4,251… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 3 publications
0
23
1
Order By: Relevance
“…We excluded a further 3656 after screening the titles and abstracts, and retrieved 109 papers for full-text review (κ value = 0.25, 95% confidence interval [CI] 0.22-0.28, indicating fair agreement according to Fleiss 9 ). Nine articles fulfilled the inclusion criteria (Figure 1), 5,[10][11][12][13][14][15][16][17] (κ = 0.83, 95% CI 0.64-1.00, indicating almost perfect agreement). Two additional studies 18,19 were identified in the weekly automated search updates, for a total of 11 included studies.…”
Section: Study Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…We excluded a further 3656 after screening the titles and abstracts, and retrieved 109 papers for full-text review (κ value = 0.25, 95% confidence interval [CI] 0.22-0.28, indicating fair agreement according to Fleiss 9 ). Nine articles fulfilled the inclusion criteria (Figure 1), 5,[10][11][12][13][14][15][16][17] (κ = 0.83, 95% CI 0.64-1.00, indicating almost perfect agreement). Two additional studies 18,19 were identified in the weekly automated search updates, for a total of 11 included studies.…”
Section: Study Selectionmentioning
confidence: 99%
“…Four before-after studies used administrative data 5,18 and chart reviews 10,13 to explore differences in outcomes before and after access to a PPCP. Three of the studies compared outcomes in the same group of patients before and after program enrolment and included children with life-threatening conditions.…”
mentioning
confidence: 99%
See 3 more Smart Citations